Information Literacy Service: SWOT Analysis - Efthymiou, Foteini; Kapnizou, Maria; Kokkinos, Dionysis; Sisamaki, Evgenia (Journal of Integrated Information Management, 2019)
Purpose - Information Literacy (IL) has nowadays a primary and substantial role within Academic Libraries worldwide. The Central Library of the National Technical University of Athens (NTUA) has developed the Service “Information Literacy Workshops”. The purpose of this paper is to describe the development of an Information Literacy (IL) Service in the context of a Hellenic Academic Library, by discussing the Strengths, Weaknesses, Opportunities and Threats that this project’s team encountered. Design/methodology/approach – Five IL workshop cycles took place in the NTUA Central Library. The first cycle was addressed to the NTUA library staff, endeavoring to establish a “learning organization” culture; three cycles were addressed to the NTUA graduate students and one cycle to post-graduate students. Each IL workshop cycle was designed, implemented and evaluated after consideration, study and adaptation of the international IL standards and strategies, as well as of four learning theories (Behaviorism, Social/Cognitive Behaviorism, Cognitivism and Constructivism) and by utilizing services and tools developed in the past by HEAL-Link within the framework of the Program “Digital Convergence”. Findings - The library, as part of an interconnected academic ecosystem, and because the volume of data available on the Internet is shockingly high and constantly increasing, should evolve and enhance its viability mainly through its intra and extra institutional collaborations and through its active involvement in the curriculum design with a vision to establish an “information literacy” culture. Originality/value – This paper enhances academic librarians’ understanding of an IL Service’s development in three ways: firstly, by narrating a real story with failures and successes and thus offering the chance to reflect upon them; secondly, by deepening in this project’s design, implementation and evaluation; thirdly, by proposing better practices that could urge Hellenic Academic Libraries to create from scratch their own IL Service or to develop their existed one further.